A new traction device (S-O clip) facilitating the endoscopic submucosal dissection of tumors in the ileocecal valve region - Yu, Shangrui; Wang, Pengfei; Feng, Yanhu (Zeitschrift für Gastroenterologie, 2022)
Background Endoscopic submucosal dissection (ESD) is a method that can be used for en bloc resection, regardless of the size and form of the lesion. The special location of ileocecal tumors leads to insufficient counter-traction and poor field of vision, making ESD difficult. An S-O clip has been developed to simplify the attachment procedure, eliminating interference with the endoscope and improving accessibility.Case presentation The patient was a 70-year-old man who presented with abdominal pain and bloating. A colonoscopy revealed a flat-elevated-type lesion on the ileocecal valve, with the oral side of the lesion having progressed to the terminal ileum. The traction direction was adjusted from distal to proximal during the procedure using the S-O clip. Finally, with the help of the S-O clip, the tumor was safely removed and collected.Conclusion The S-O clip was successful in ESD of a colorectal tumor. By removing and re-anchoring the loaded ring, the S-O clips allowed the adjustment of traction direction from distal to proximal during ESD.
Keywords: neues Traktionsgerät; S-O-Clip; ESD; ileozökal